A study on the prevalence of acute and chronic malnutrition and influence of feeding practices among 6 months to 2 years children in rural field practice area of Kilpauk Medical College, Tamil Nadu - Dhanalakshmi, S.; Selvaraj, R. (International Journal Of Community Medicine And Public Health, 2019)
Background: In India, 54% of under five children death mainly due to under nutrition. First two years of age is most critical. Nutritional status was assessed by using WHO standard growth chart. Wasting represents acute malnutrition, stunting with chronic, underweight represents both acute and chronic. Based on NFHS-3 data the prevalence of under nutrition rise up to 2 years of age, thereafter more or less stabilizes. Faulty feeding practices plays major role in under nutrition. Hence, this study carried out to assess nutritional status of 6 months to 2 years children in terms of acute and chronic malnutrition and to estimate the association of nutritional status with feeding practices. Methods: Cross sectional study done during March to August 2016. Sample size estimated was 180. Stratified random sampling method used to collect data among children in Peerkankaranai. Results: Mean age of children was 15.82 months. About 61.2% belonged to 12 to 24 months age group. Sex distributions were equal. About 55% belongs to middle socioeconomic status. The prevalence of underweight was 31.65, wasting 15%, stunting 45.6%. Male children affected by chronic malnutrition more than female children. Not initiating breast feeding within 4 hours of birth plays significant role in acute malnutrition. Prevalence of malnutrition was high among those not practising colostrum feeding and exclusive breast feeding. Only 15 mothers not influenced by formula feeding. Feeding frequency and traditional feeding practices had main role in chronic malnutrition. Conclusions: The prevalence of under nutrition among study population was high among this area. Feeding practices should be improved among the mothers.